Word and number puzzles linked to higher cognitive function. (2nd July 2019) - Palmer, Sarah
Abstract : Cognitive stimulation is often advised to delay or slow down dementia. An ongoing study is now trying to establish a clear link between doing puzzles and better cognitive function. Sarah Palmer sets out the objectives and results of the study.